FOREIGN EXPERIENCE OF ORGANIZING QUALITY MANAGEMENT IN SECONDARY EDUCATION SYSTEM - Shahobinnova Malohat (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
In the scientific article, the scientific research conducted in the practice of the educational system in developed foreign countries, the cases of differences in content and essence of the microfields used in general secondary education are analyzed. At the third stage of the education system in foreign countries, the aspects of operation of each educational institution based on its own democratic principles were studied and suggestions for implementation in our country were developed based on foreign experiences.